The Modernist Mirror and the Hold of Being: Rilke and Zamiatin - Petre Petrov (Studies in 20th & 21st Century Literature, 2010)
The article approaches the image of the mirror as a metaphorical vehicle for the experience of modernity in the work of Rainer Maria Rilke and Evgenii Zamiatin. The argument builds upon a duality that informs the folkloric and artistic representations of mirrors from ancient to modern times: that between flat and deep reflection. Flat reflection refers to the idea of images projected outwardly from the specular surface, while deep reflection implies an imaginary space behind this surface, where objects are caught and held. By examining two of Rilke’s elegies and Zamiatin’s novel We, the article shows the way in which the mirror becomes a symbolic topos for the anxieties of modernization and the redemptive ambitions of modernist writing. For both Rilke and Zamiatin, the deep mirror becomes a figurative stand-in for art and the professed power of artistic representation to re-establish a severed connection with being.
Keywords: mirror; modernity; Rainer Maria Rilke; Evgenii Zamiatin; elegies; We; symbolic topos; anxieties of modernization; art